(untitled) (Fiep Bulletin - online, 2014)
The purpose of this study was to investigate the outcome of Physical Education activities on reduction of Unilateral Neglect in hemiplegic students attacked by stroke, who participates on the Motor Activities Program for Disables (PROAMDE), moreover to watchful the subject’s corporal perception. For that reason, it was realized an semi-structured interview on beginning of the search, recorded on K7 tape, who was repeated on the end of the program, to further transcription and interpretation of datas through analysis of contents technique. The outcome during physical education activities was verified By a motor assessment, not validated, criated by our own way, and analysed descriptively. From three students analyzed, no one manifests completely the Neglect Syndrome, however, all they show a segregated image of their self bodies, where one side, the affected, they reject wholly. Therefore, we believe this self negative body image can being changed through a most utilization of this side.